Microbial respiration and soil acidity under liming and organomineral amendment - González-Pedraza, Ana; Vivas , Cristian; Aragón , Claudia; Escalante, Juan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Soil acidity severely limits biological activity in high Andean systems, where aluminum toxicity and low pH reduce agricultural productivity and constrain microbial processes. In this context, the effect of calcium carbonate (CaCO₃), applied both individually and in combination with a commercial organo-mineral amendment, was evaluated on soil pH, exchangeable aluminum, and microbial respiration in an acidic soil collected from an agricultural farm located in the mountainous region of Pamplona (Norte de Santander), through a 15 day controlled incubation conducted between March and May 2021. A completely randomized design with four treatments (control, 100 % CaCO3, 50 % CaCO3, and 50 % CaCO3 + amendment) and five replicates per treatment was used, measuring chemical variables and respiration at multiple incubation times; statistical analyses included ANOVA, Spearman correlations, and multiple linear regressions. Results showed that CaCO3 significantly increased pH (up to +0.62 units at the full dose) and reduced exchangeable aluminum only in this treatment, while all amended treatments enhanced microbial respiration, particularly during early stages, with a tendency toward a stronger response in the organic combination. However, multivariate analysis revealed that chemical variables did not independently explain respiratory variability, highlighting the predominance of the integrated treatment effect. It is concluded that liming, especially when combined with organic amendments, corrects chemical acidity and revitalizes microbial activity through systemic effects, with practical implications for the sustainable management of high Andean soils.